Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve each part of the question step-by-step:
(a) \( A \cap (B - C) \)
First, we need to find the difference between sets \( B \) and \( C \):
[tex]\[ B - C = \{ x \mid x \in B \text{ and } x \notin C \} = \{6, 8, 9\} \][/tex]
Now, we find the intersection of \( A \) with \( B - C \):
[tex]\[ A \cap (B - C) = \{ x \mid x \in A \text{ and } x \in (B - C) \} = \{8\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{8\}} \][/tex]
(b) \( A - (B - C) \)
Using the result from part (a) for \( B - C = \{6, 8, 9\} \), we find the difference between sets \( A \) and \( B - C \):
[tex]\[ A - (B - C) = \{ x \mid x \in A \text{ and } x \notin (B - C) \} = \{1, 4, 7\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 4, 7\}} \][/tex]
(d) \( A^c \cap (B^c - C^c) \)
First, we find the complements of \( A \), \( B \), and \( C \) in the universal set \( U \):
[tex]\[ A^c = U - A = \{2, 3, 5, 6, 9\} \][/tex]
[tex]\[ B^c = U - B = \{1, 2, 3, 5, 7\} \][/tex]
[tex]\[ C^c = U - C = \{1, 2, 6, 8, 9\} \][/tex]
Next, we find the difference between \( B^c \) and \( C^c \):
[tex]\[ B^c - C^c = \{ x \mid x \in B^c \text{ and } x \notin C^c \} = \{3, 5\} \][/tex]
Now, we find the intersection of \( A^c \) with \( B^c - C^c \):
[tex]\[ A^c \cap (B^c - C^c) = \{ x \mid x \in A^c \text{ and } x \in (B^c - C^c) \} = \{3, 5\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{3, 5\}} \][/tex]
(e) \( A \cup (B \cap C^c) \)
Using the complement of \( C \) found previously \( C^c = \{1, 2, 6, 8, 9\} \), we find the intersection of \( B \) with \( C^c \):
[tex]\[ B \cap C^c = \{ x \mid x \in B \text{ and } x \in C^c \} = \{6, 8, 9\} \][/tex]
Now, we find the union of \( A \) with \( B \cap C^c \):
[tex]\[ A \cup (B \cap C^c) = \{ x \mid x \in A \text{ or } x \in (B \cap C^c) \} = \{1, 4, 6, 7, 8, 9\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 4, 6, 7, 8, 9\}} \][/tex]
(c) \( A \cup B^c \)
Using the complement of \( B \) found previously \( B^c = \{1, 2, 3, 5, 7\} \), we find the union of \( A \) with \( B^c \):
[tex]\[ A \cup B^c = \{ x \mid x \in A \text{ or } x \in B^c \} = \{1, 2, 3, 4, 5, 7, 8\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 2, 3, 4, 5, 7, 8\}} \][/tex]
(f) \( (A - C) \cup (C - A) \)
First, we find the difference between sets \( A \) and \( C \):
[tex]\[ A - C = \{ x \mid x \in A \text{ and } x \notin C \} = \{1, 8\} \][/tex]
Next, we find the difference between sets \( C \) and \( A \):
[tex]\[ C - A = \{ x \mid x \in C \text{ and } x \notin A \} = \{3, 5\} \][/tex]
Now, we find the union of \( A - C \) and \( C - A \):
[tex]\[ (A - C) \cup (C - A) = \{1, 8\} \cup \{3, 5\} = \{1, 3, 5, 8\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 3, 5, 8\}} \][/tex]
(a) \( A \cap (B - C) \)
First, we need to find the difference between sets \( B \) and \( C \):
[tex]\[ B - C = \{ x \mid x \in B \text{ and } x \notin C \} = \{6, 8, 9\} \][/tex]
Now, we find the intersection of \( A \) with \( B - C \):
[tex]\[ A \cap (B - C) = \{ x \mid x \in A \text{ and } x \in (B - C) \} = \{8\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{8\}} \][/tex]
(b) \( A - (B - C) \)
Using the result from part (a) for \( B - C = \{6, 8, 9\} \), we find the difference between sets \( A \) and \( B - C \):
[tex]\[ A - (B - C) = \{ x \mid x \in A \text{ and } x \notin (B - C) \} = \{1, 4, 7\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 4, 7\}} \][/tex]
(d) \( A^c \cap (B^c - C^c) \)
First, we find the complements of \( A \), \( B \), and \( C \) in the universal set \( U \):
[tex]\[ A^c = U - A = \{2, 3, 5, 6, 9\} \][/tex]
[tex]\[ B^c = U - B = \{1, 2, 3, 5, 7\} \][/tex]
[tex]\[ C^c = U - C = \{1, 2, 6, 8, 9\} \][/tex]
Next, we find the difference between \( B^c \) and \( C^c \):
[tex]\[ B^c - C^c = \{ x \mid x \in B^c \text{ and } x \notin C^c \} = \{3, 5\} \][/tex]
Now, we find the intersection of \( A^c \) with \( B^c - C^c \):
[tex]\[ A^c \cap (B^c - C^c) = \{ x \mid x \in A^c \text{ and } x \in (B^c - C^c) \} = \{3, 5\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{3, 5\}} \][/tex]
(e) \( A \cup (B \cap C^c) \)
Using the complement of \( C \) found previously \( C^c = \{1, 2, 6, 8, 9\} \), we find the intersection of \( B \) with \( C^c \):
[tex]\[ B \cap C^c = \{ x \mid x \in B \text{ and } x \in C^c \} = \{6, 8, 9\} \][/tex]
Now, we find the union of \( A \) with \( B \cap C^c \):
[tex]\[ A \cup (B \cap C^c) = \{ x \mid x \in A \text{ or } x \in (B \cap C^c) \} = \{1, 4, 6, 7, 8, 9\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 4, 6, 7, 8, 9\}} \][/tex]
(c) \( A \cup B^c \)
Using the complement of \( B \) found previously \( B^c = \{1, 2, 3, 5, 7\} \), we find the union of \( A \) with \( B^c \):
[tex]\[ A \cup B^c = \{ x \mid x \in A \text{ or } x \in B^c \} = \{1, 2, 3, 4, 5, 7, 8\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 2, 3, 4, 5, 7, 8\}} \][/tex]
(f) \( (A - C) \cup (C - A) \)
First, we find the difference between sets \( A \) and \( C \):
[tex]\[ A - C = \{ x \mid x \in A \text{ and } x \notin C \} = \{1, 8\} \][/tex]
Next, we find the difference between sets \( C \) and \( A \):
[tex]\[ C - A = \{ x \mid x \in C \text{ and } x \notin A \} = \{3, 5\} \][/tex]
Now, we find the union of \( A - C \) and \( C - A \):
[tex]\[ (A - C) \cup (C - A) = \{1, 8\} \cup \{3, 5\} = \{1, 3, 5, 8\} \][/tex]
Thus, the answer is:
[tex]\[ \boxed{\{1, 3, 5, 8\}} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.